Difficult pediatric airway in anesthesia practice and future sport performance - Łepik, Michał; Uszok, Zofia; Rosiak, Krzysztof; Płeska, Kacper; Reguła, Kacper; Waloch, Kamil; Wojtania, Joanna; Piaszczyński, Szymon; Czajka, Andrzej; Szymański , Bartłomiej (Quality in Sport, 2024)
Difficult pediatric airways can present significant challenges in clinical practice and cause consequences for sport performance. Etiologies of difficult pediatric airways can range from congenital abnormalities, acquired conditions such as trauma or inflammation, systemic diseases such as neuromuscular disorders and craniofacial abnormalities to iatrogenic causes including complications of airway interventions and anesthetic complications. Proper assessment of difficult airways risk requires a thorough understanding of the anatomical and physiological differences in pediatric patients. Assessment of Management strategies may include adequate non-invasive techniques, advanced airway devices, pharmacological interventions, surgical interventions, continuous monitoring with extensive postoperative care provided by a multidisciplinary team, involving pediatric anesthesiologists, otolaryngologists, pediatricians, and critical care specialists. Difficult airway in anesthesia practice may lead to mild to life-threatening complications such as difficult mask ventilation, failed intubation, esophageal intubation, airway trauma, hypoxia, hypercarbia, aspiration, barotrauma, difficult extubation, unoptimal sedation or anesthesia, postoperative complications and other consequences. All of this can be a predictor of decreased respiratory efficiency, and thus a predictor of low future athletic performance in children and may have a negative impact on future career choices. This comprehensive overview aims to provide insights into the etiologies, assessment, and management strategies for difficult pediatric airways, with a focus on optimizing patient outcomes and safety and to help understand potential influence on future sport performance.